2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00885
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Diverse Sampling of Sequences Based on a "Best of Many" Sample Objective

Abstract: For autonomous agents to successfully operate in the real world, anticipation of future events and states of their environment is a key competence. This problem has been formalized as a sequence extrapolation problem, where a number of observations are used to predict the sequence into the future. Real-world scenarios demand a model of uncertainty of such predictions, as predictions become increasingly uncertainin particular on long time horizons. While impressive results have been shown on point estimates, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 10 publications
0
101
0
Order By: Relevance
“…They showed that minimizing the RWTA loss is able to capture the possible futures for a car approaching a road crossing, i.e., going straight, turning left, and turning right. Bhattacharyya et al [3] set up this optimization within an LSTM network for future location prediction. Despite capturing the future locations, these works do not provide the whole distribution over the possible locations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that minimizing the RWTA loss is able to capture the possible futures for a car approaching a road crossing, i.e., going straight, turning left, and turning right. Bhattacharyya et al [3] set up this optimization within an LSTM network for future location prediction. Despite capturing the future locations, these works do not provide the whole distribution over the possible locations.…”
Section: Related Workmentioning
confidence: 99%
“…Also statistical information on how bicyclists moved in the past in this round- Figure 1: Given the past images, the past positions of an object (red boxes), and the experience from the training data, the approach predicts a multimodal distribution over future states of that object (visualized by the overlaid heatmap). The bicyclist is most likely to move straight (1), but could also continue on the roundabout (2) or turn right (3). about and potentially subtle cues like the orientation of the bicycle and its speed can indicate where a bicyclist is more likely to go.…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches actually targeting multi-modal prediction are given by e.g. (Bhattacharyya, Schiele, and Fritz 2018) and (Hug et al 2018).…”
Section: Multi-step Predictionmentioning
confidence: 99%
“…[15] applied the Hidden Markov Model (HMM) to predict the trajectories for individual driver. [16] combined CNN and LSTM to predict multi-modal trajectories for an agent on a bird-view image. The main limitation of these works, however, is that they only predict motions for one selected agent without considering the influence of other agents with potential interactions.…”
Section: Trajectory Predictionmentioning
confidence: 99%